Classification of Harmful Educational Practices Based on Shahid Motahhari’s Theory of the Perfect Human - Meysam Sedaghatzadeh (پژوهش در آموزش معارف و تربیت اسلامی)
One of the essential needs of any civilization is human education, and every educational system requires a theory. Educational theories are shaped by specific philosophical perspectives, which negate other theories of education based on their philosophical foundations. In this regard, the present study aims to address the question: what are the types of incorrect and harmful educational practices in the path toward developing the perfect human, and how can they be classified? The study focuses on Shahid Motahhari's significant role in contemporary Islamic theorization. To this end, all of Shahid Motahhari’s works were analyzed using a qualitative analytical method. The findings reveal that in the process of educating the perfect human, four types of harmful educational practices may occur: Non-human education, which deviates from innate human tendencies (fiṭrah), leading to individuals conforming to the desires of the educator rather than aligning with their creation. Incomplete education, which focuses only on certain aspects of human existence rather than a comprehensive approach. Unhealthy education, which lacks balance, ultimately producing a caricature-like personality. Imperfect education, which results in a model of human development that falls short of achieving true perfection.